2012
DOI: 10.1038/mp.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness of superior frontal cortex predicts impulsiveness and perceptual reasoning in adolescence

Abstract: Impulsiveness is a pivotal personality trait representing a core domain in all major personality inventories. Recently, impulsiveness has been identified as an important modulator of cognitive processing, particularly in tasks that require the processing of large amounts of information. Although brain imaging studies have implicated the prefrontal cortex to be a common underlying representation of impulsiveness and related cognitive functioning, to date a fine-grain and detailed morphometric analysis has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 91 publications
12
70
5
2
Order By: Relevance
“…Our finding that the young adult ER subjects had previously reported more externalizing behaviors is consistent with prior working showing associations between externalizing measures and substance abuse risk (Benegal et al, 2007; Bava and Tapert, 2010). In addition, the negative associations between these early adolescent behavior scores and the subjects’ current frontal cortical volumes are in agreement with a recent report that left superior frontal cortical thickness in adolescents was negatively related to impulsiveness, another behavioral measure associated with risk (Schilling et al, 2013). The substance risk variable used in this study was created from measures of early engagement with substances, so, in agreement with the early externalizing measures, further links early behaviors with frontal cortical volumes.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that the young adult ER subjects had previously reported more externalizing behaviors is consistent with prior working showing associations between externalizing measures and substance abuse risk (Benegal et al, 2007; Bava and Tapert, 2010). In addition, the negative associations between these early adolescent behavior scores and the subjects’ current frontal cortical volumes are in agreement with a recent report that left superior frontal cortical thickness in adolescents was negatively related to impulsiveness, another behavioral measure associated with risk (Schilling et al, 2013). The substance risk variable used in this study was created from measures of early engagement with substances, so, in agreement with the early externalizing measures, further links early behaviors with frontal cortical volumes.…”
Section: Discussionsupporting
confidence: 90%
“…This theory was further supported by studies showing that higher scores in measures of intelligence were related to higher gray matter volume in these areas (Colom et al, 2009;Karama et al, 2009;Johnson, Jung, Colom, & Haier, 2008). Recently, higher cortical thickness of the superior frontal cortex has been proposed as common neural basis of intelligence and impulsivity (Schilling et al, 2013) indicating a potential overlap in brain networks underlying both behaviors.…”
Section: Neural Correlates Of Intelligence and Their Relation To Intementioning
confidence: 84%
“…Several recent studies have found thinner cortex to be predictive of favorable cognitive development in school age years in a variety of cognitive domains (31-37), as well as in neurodevelopmental conditions such as schizophrenia (28,38). However, it is important to note that also positive associations between cognitive function and cortical thickness have been found in childhood and adolescence (39,40) and that symptoms of neurodevelopmental conditions and risk factors have been associated with thinner cortex as well (41)(42)(43)(44), even in age-varying ways (45,46) [see Vuoksimaa et al for a more in-depth discussion on the relationship between cortical thickness and general cognitive abilities (47)]. These different effects may be due to offset differences between groups and/ or differences in change rates and indicate a complex relationship between symptoms and cortical developmental markers (48,49) that likely depends on the condition in question, cortical region, and age.…”
Section: Discussionmentioning
confidence: 99%